Water-Handling Patterns and Associated Microbial Profiles in relation to Hygiene in Babati Town, Tanzania. (20th May 2019) - Tesha, Irene; Machunda, Revocatus; Njau, Karoli; Mpolya, Emmanuel
Abstract : Introduction . In rapidly urbanizing centres in Tanzania, water supply infrastructure lags behind the speed of urbanization, affecting water availability and accessibility. We believe that inhabitants' access water using various ways which are characterizable and understanding them could inform about the risks to hygiene-related diseases. This study aimed at characterizing water-handling chains and their microbial profiles in Babati town to inform hygiene education policy and water supply planning. Methodology . A cross-sectional study design employing a proportional sampling for each of the 8 wards was conducted between November 2016 and March 2017. A total of 564 samples of water were collected using the USA EPA procedures from 37 randomly selected households. Water samples were collected from the common sources of water as well as from the downstream points to multiple storage containers. Using EPA membrane filtration techniques, two microorganisms were tested: fecal coliforms and Salmonella typhi. Results . Three water-handling chains/patterns in Babati town were determined, and they were as follows: (i) untreated-source-to-treated-reservoir-to-households ( untrS2trR2HH ) chain, (ii) untreated-source-to-untreated-reservoir-to-households ( untrS2untrR2HH ) chain; (iii) untreated-source-straight-to-households ( untrS2HH ) chain. In terms of the microbial profile, the most contaminated water-handling chain was the untreated-source-straight-to-households ( untrS2HH ). The number of users in these three chains was not statistically significantly different (p = 0.5226 ), meaning that all people utilized the various chains almost equally, depending on the water situation. Most households (83%) did not treat their drinking water making those using the untreated-source-to-household chain ( untrS2HH ) most vulnerable to waterborne diseases. Conclusion . Determination of water-handling chains among the household is a novel approach which allows an understanding of the points at which highest fecal loading occurs. This approach therefore may inform the development of policies in the areas of household hygiene education, drinking water treatment, and water supply planning in urbanized towns in Tanzania and other developing countries.